2011
DOI: 10.1109/jstsp.2010.2104312
|View full text |Cite
|
Sign up to set email alerts
|

Local Signal-Dependent Noise Variance Estimation From Hyperspectral Textural Images

Abstract: International audienceA maximum-likelihood method for estimating hyperspectral sensors random noise components, both dependent and independent from the signal, is proposed. A hyperspectral image is locally jointly processed in the spatial and spectral dimensions within a multicomponent scanning window (MSW), as small as 7 x 7 x 7 spatial-spectral pixels. Each MSW is regarded as an additive mixture of spectrally correlated fractal Brownian motion (fBm)-samples and random noise. The main advantage of the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 42 publications
0
79
0
Order By: Relevance
“…As can be clearly seen from Figure 1, the noise level of the five representative bands is different, and the noise levels of bands 1 and 220 are obviously higher than those of the other three bands. Besides, the previous works correlated with noise estimation of HSI [52][53][54] have demonstrated that the hyperspectral imaging spectrometers adopt very narrow band, which makes the energy acquired in each band not enough to obtain high signal-to-noise ratio (SNR), and the HSI is usually corrupted by wavelength-dependent and sensor-specific noise, which not only degrades the visual quality of the HSI but also limits the precision of the subsequent image interpretation and analysis. That is to say, the noise of HSI is wavelength-dependent, thus the noise levels of different bands are different.…”
Section: The Proposed Su-nlementioning
confidence: 99%
See 1 more Smart Citation
“…As can be clearly seen from Figure 1, the noise level of the five representative bands is different, and the noise levels of bands 1 and 220 are obviously higher than those of the other three bands. Besides, the previous works correlated with noise estimation of HSI [52][53][54] have demonstrated that the hyperspectral imaging spectrometers adopt very narrow band, which makes the energy acquired in each band not enough to obtain high signal-to-noise ratio (SNR), and the HSI is usually corrupted by wavelength-dependent and sensor-specific noise, which not only degrades the visual quality of the HSI but also limits the precision of the subsequent image interpretation and analysis. That is to say, the noise of HSI is wavelength-dependent, thus the noise levels of different bands are different.…”
Section: The Proposed Su-nlementioning
confidence: 99%
“…To overcome the above mentioned problem, according to the Figure 1 and the previous works correlated with noise estimation of HSI [52][53][54], it is natural to assume that the noise levels at different bands are different. We adopt a simple and efficient noise estimation method based on the multiple regression theory, developed by Bioucas and Nascimento [52], to estimate the noise in each band of HSI.…”
Section: The Proposed Su-nlementioning
confidence: 99%
“…Due to the high spectral resolution of HS spectrometers, the useful image signal exhibits strong correlations between spectral bands. In contrast, the noise signal is often modelled as a random process that is spatially and spectrally uncorrelated [20][21][22]. The random noise in HS images can be described as:…”
Section: Parametric Noise Modelmentioning
confidence: 99%
“…In this experiment, SD and SI noise are added to the synthetic HS image with SNR = 30 and SDSINR = 1, where the true values of parameters γ sd,p and σ 2 si,p can be obtained according to Equations (21) and (22). The proposed FSSMNE is compared with other three state-of-the-art noise estimation methods, including HS noise parameter estimation (HSNPE) [20], signal-dependent noise estimation (SDNE) [24], and intensity-variance homogeneity classification-based noise estimation (IVHCNE) [25].…”
Section: Experiments On the Synthetic Hs Imagementioning
confidence: 99%
“…In this paper, only noise estimation algorithms based on signal independent model are analyzed and assessed. There are also some new algorithms with signal dependent model lately [16], [17]. These algorithms are not discussed in this paper.…”
Section: Linear Regression-based Noise Estimation Algrithmsmentioning
confidence: 99%